Recombinant probiotic therapy in experimental colitis in mice - Gardlik, R; Palffy, R; Celec, P (Folia biologica, 2012)
Recently, high interest has been attracted to the research of inflammatory bowel diseases (IBD). Recombinant probiotic bacteria may represent an interesting way to influence the course of IBD. Their benefits include cheap and simple production and easy manipulation of the genetic material. Several gene therapy and probiotic approaches already showed promising results in the past. The aim of this study was to test the probiotic potential of IL-10-expressing Escherichia coli Nissle 1917 in a mouse model of IBD and to compare it with control bacterial strains. The dextran sulphate sodium (DSS) model of colitis was examined for this purpose. Animals received control probiotic bacteria or modified probiotics (expressing IL-10) via gastric gavage. Body weight, stool consistency, food and water consumption were monitored. At the end of the experiment, the parameters of inflammation, oxidative stress and carbonyl stress were analysed in the samples and statistical analysis was performed. We prepared an anti-inflammatory probiotic Escherichia coli strain that we designated Nissle 1917/pMEC-IL10 and proved its anti-inflammatory properties, which are similar to those of the control probiotic strains Nissle 1917 and Lactococcus lactis/pMEC-IL10 in vivo. The probiotic therapy was successful according to several parameters, including colon length, and oxidative and carbonyl stress. Bacterially produced IL-10 was detected in the plasma. The potential of bacterial anti-inflammatory therapy of IBD using modified probiotics was outlined. The results opened a way for upcoming studies using modified probiotics for therapy of systemic diseases.
Keywords: Protein Carbonylation; probiotika; fruktosamin; Oxidative Stress; kolitida; myši; Feces; Fructosamine; Mice; karbonylace proteinů; Interleukin-10; Colon; Disease Models, Animal; Colitis; feces; mužské pohlaví; interleukin-10; kolon; zvířata; Mice, Inbred C57BL; rekombinantní proteiny; oxidační stres; Recombinant Proteins; Animals; Male; Malondialdehyde; tělesná hmotnost; modely nemocí na zvířatech; malondialdehyd; Probiotics; myši inbrední C57BL; Body Weight